Benthic microfossils from the Tepla-Barrandian Late Proterozoic (Blovice Formation, Czech Republic) - Vavrdova,M. (Journal of the Czech Geological Society, 1999)
Dark carbonaceous cherts from the Blovice Formation (Kralupy-Zbraslav Group, Tepla-Barrandian Late Proterozoic) contain planktonic and benthic types of silicified microbiota, organo-sedimentary textures and structures and other evidence of locally preserved sequences which originated in near-shore, littoral environment. Microfossils were studied in 200 thin sections, as palynological residua and by SEM rock-surface observation. Three successive generations of silicites can be distinguished, based on both mat-forming benthic and planktonic microfossils. Depositional environment includes subtidal shelves, oolitic shoals, hypersaline lagoons and supratidal algal marshes. Silicified stromatolitic algal breccias, oolitic limestones and silicified biostromes and presumed layered evaporites have been investigated. Agglomerations of coccoid, filamentous, colonial and vase-shaped microfossils are described.
Keywords: Late Proterozoic; Blovice Formation; stromatolites; silicified biota; palaeoecology